The Birthplace in England national prospective cohort study: further analyses to enhance policy and service delivery decision-making for planned place of birth - Jennifer Hollowell; Rachel Rowe; John Townend; Marian Knight; Yangmei Li; Louise Linsell; Maggie Redshaw; Peter Brocklehurst; Alison Macfarlane; Neil Marlow; Christine McCourt; Mary Newburn; et al. (National Institute for Health Research, 2015)
Background: Evidence from the Birthplace in England Research Programme supported a policy of offering 'low risk' women a choice of birth setting, but a number of unanswered questions remained. Aims: This project aimed to provide further evidence to support the development and delivery of maternity services and inform women's choice of birth setting: specifically, to explore maternal and organisational factors associated with intervention, transfer and other outcomes in each birth setting in 'low risk' and 'higher risk' women. Design: Five component studies using secondary analysis of the Birthplace prospective cohort study (studies 2-5) and ecological analysis of unit/NHS trust-level data (studies 1 and 5). Setting: Obstetric units (OUs), alongside midwifery units (AMUs), freestanding midwifery units (FMUs) and planned home births in England. Participants: Studies 1-4 focused on 'low risk' women with 'term' pregnancies planning vaginal birth in 43 AMUs (n = 16,573), in 53 FMUs (n = 11,210), at home in 147 NHS trusts (n = 16,632) and in a stratified, random sample of 36 OUs (n = 19,379) in 2008-10. Study 5 focused on women with pre-existing medical and obstetric risk factors ('higher risk' women). Main outcome measures: Interventions (instrumental delivery, intrapartum caesarean section), a measure of low intervention ('normal birth'), a measure of spontaneous vaginal birth without complications ('straightforward birth'), transfer during labour and a composite measure of adverse perinatal outcome ('intrapartum-related mortality and morbidity' or neonatal admission within 48 hours for > 48 hours). In studies 1 and 3, rates of intervention/maternal outcome and transfer were adjusted for maternal characteristics. Analysis: We used (a) funnel plots to explore variation in rates of intervention/maternal outcome and transfer between units/trusts, (b) simple, weighted linear regression to evaluate associations between unit/trust characteristics and rates of intervention/maternal outcome and transfer, (c) multivariable Poisson regression to evaluate associations between planned place of birth, maternal characteristics and study outcomes, and (d) logistic regression to investigate associations between time of day/day of the week and study outcomes. Results: Study 1 - unit-/trust-level variations in rates of interventions, transfer and maternal outcomes were not explained by differences in maternal characteristics. The magnitude of identified associations between unit/trust characteristics and intervention, transfer and outcome rates was generally small, but some aspects of configuration were associated with rates of transfer and intervention. Study 2 - 'low risk' women planning non-OU birth had a reduced risk of intervention irrespective of ethnicity or area deprivation score. In nulliparous women planning non-OU birth the risk of intervention increased with increasing age, but women of all ages planning non-OU birth experienced a reduced risk of intervention. Study 3 - parity, maternal age, gestational age and 'complicating conditions' identified at the start of care in labour were independently associated with variation in the risk of transfer in 'low risk' women planning non-OU birth. Transfers did not vary by time of day/day of the week in any meaningful way. The duration of transfer from planned FMU and home births was around 50-60 minutes; transfers for 'potentially urgent' reasons were quicker than transfers for 'non-urgent' reasons. Study 4 - the occurrence of some interventions varied by time of the day/day of the week in 'low risk' women planning OU birth. Study 5 - 'higher risk' women planning birth in a non-OU setting had fewer risk factors than 'higher risk' women planning OU birth and these risk factors were different. Compared with 'low risk' women planning home birth, 'higher risk' women planning home birth had a significantly increased risk of our composite adverse perinatal outcome measure. However, in 'higher risk' women, the risk of this outcome was lower in planned home births than in planned OU births, even after adjustment for clinical risk factors. Conclusions: Expansion in the capacity of non-OU intrapartum care could reduce intervention rates in 'low risk' women, and the benefits of midwifery-led intrapartum care apply to all 'low risk' women irrespective of age, ethnicity or area deprivation score. Intervention rates differ considerably between units, however, for reasons that are not understood. The impact of major changes in the configuration of maternity care on outcomes should be monitored and evaluated. The impact of non-clinical factors, including labour ward practices, staffing and skill mix and women's preferences and expectations, on intervention requires further investigation. All women planning non-OU birth should be informed of their chances of transfer and, in particular, older nulliparous women and those more than 1 week past their due date should be advised of their increased chances of transfer. No change in the guidance on planning place of birth for 'higher risk' women is recommended, but research is required to evaluate the safety of planned AMU birth for women with selected relatively common risk factors. Funding: The National Institute for Health Research Health Services and Delivery Research programme.